2015
DOI: 10.1042/bj20141021
|View full text |Cite
|
Sign up to set email alerts
|

RECQ1 interacts with FEN-1 and promotes binding of FEN-1 to telomeric chromatin

Abstract: RecQ helicases are a family of highly conserved proteins that maintain genomic stability through their important roles in replication restart mechanisms. Cellular phenotypes of RECQ1 deficiency are indicative of aberrant repair of stalled replication forks, but the molecular functions of RECQ1, the most abundant of the five known human RecQ homologs, have remained poorly understood. We show that RECQ1 associates with FEN-1 in nuclear extracts and exhibits direct protein interaction in vitro. Recombinant RECQ1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 78 publications
1
15
0
Order By: Relevance
“…Notably, RECQ1-C453A, RECQ1-C475A, and RECQ1-C478A mutants failed to unwind fork duplex and no detectable unwinding of the fork duplex was observed even at the excessively increased protein concentration (160 nM) (Figure 2A and 2B). Consistent with their inability to unwind fork duplex, RECQ1 variants RECQ1-C453A, RECQ1-C475A and RECQ1-C478A failed to unwind a 5’-flap substrate that mimics intermediate of DNA replication and repair and is unwound by wild-type RECQ1 [21,36]. In a control reaction and as previously reported [21], RECQ1 protein containing a K119A mutation within the helicase domain also failed to unwind 5’-flap DNA substrate.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Notably, RECQ1-C453A, RECQ1-C475A, and RECQ1-C478A mutants failed to unwind fork duplex and no detectable unwinding of the fork duplex was observed even at the excessively increased protein concentration (160 nM) (Figure 2A and 2B). Consistent with their inability to unwind fork duplex, RECQ1 variants RECQ1-C453A, RECQ1-C475A and RECQ1-C478A failed to unwind a 5’-flap substrate that mimics intermediate of DNA replication and repair and is unwound by wild-type RECQ1 [21,36]. In a control reaction and as previously reported [21], RECQ1 protein containing a K119A mutation within the helicase domain also failed to unwind 5’-flap DNA substrate.…”
Section: Resultssupporting
confidence: 70%
“…Full-length RECQ1 proteins, wild-type (RECQ1-WT) or with engineered single amino acid substitutions with alanine at conserved cysteine residues (RECQ1-C453A, RECQ1-C471A, RECQ1-C475A, and RECQ1-C478A) were overexpressed in bacteria and purified to near homogeneity using a previously reported method [25,36]. …”
Section: Resultsmentioning
confidence: 99%
“…Besides, yeast two-hybrid assays identified potential homo-and hetero-typical interactions between different P. falciparum ApiAP2 proteins as well as interaction with other P. falciparum transcriptional regulators (LaCount et al, 2005). (Sami et al, 2015). (Sami et al, 2015).…”
Section: Pfap2tel Is a Nuclear Protein That Co-localises With Telommentioning
confidence: 99%
“…The nuclear protein complex that binds to P. falciparum telomeres, in addition to PfAP2Tel, contains proteins with DNA helicase and endonuclease activities, DNA mismatch repair activity, zinc finger domains and bromodomains ( (Sami et al, 2015).…”
Section: Pfap2tel Is a Nuclear Protein That Co-localises With Telommentioning
confidence: 99%
“…Subsequent studies elucidated that RECQ1 helicase is a major player in maintaining replication fork progression under stress [912]. We have found that RECQ1 is enriched at specific genomic regions that pose significant challenge to replication and transcription, and are hotspots for instability and mutagenesis in cancer [12,13]. We reasoned that RECQ1 could be a multifunctional protein due to its high abundance and specific interactions with chromatin.…”
Section: Introductionmentioning
confidence: 99%